Policies on tuberculosis treatment: A review of healthcare strategies and interventions - fithriany fithriany (Institute of Computer Science (IOCS), 2023)
This study aims to conduct a comprehensive analysis of policies related to tuberculosis (TB) treatment, with a focus on examining healthcare strategies and interventions. A systematic literature review was employed as the research methodology to gather relevant scientific evidence from various published sources. The eligibility criteria for study inclusion were based on factors such as study type, population sample, and research quality. The search strategy involved utilizing academic journal search engines from online databases, including PubMed, Web of Science, Scopus, and Springer Link. Relevant keywords such as